The integration of dilemmas stories with STEM-project-based learning: Analyzing students' thinking skills using Hess' cognitive rigor matrix - Yuli Rahmawati; Afrizal Afrizal; Devina Dwi Astari; Alin Mardiah; Dyah Budi Utami; Sukro Muhab (OmniaScience, 2021)
This study aimed to analyze students' thinking skills through integrating dilemmas stories with a Science, Technology, Engineering, and Mathematics (STEM) project in polymers topic. The participants were 47 Grade 12 students from a public senior high school in West Java Province. The research employed a qualitative method to obtain data through classroom observations, reflective journals, interviews, and a concept test. Students' thinking skills were assessed using Hess' Cognitive Rigor Matrix, which combines Bloom's taxonomic and Webb's depth of knowledge. The results show that most students reach level C2 of Bloom's taxonomy and level 1 of Webb's depth of knowledge, meaning that most students understand and recall the information. The results indicate that integrating dilemmas stories with STEM-PjBL enables students to explain using simple sentences and prior knowledge. In addition, this approach provides an opportunity for students to develop their critical thinking, creativity, and argumentation skills through problem-solving and project making.